British imbalance market paradox: variable renewable energy penetration in energy markets - Atherton, John (2024)
The expansion of variable renewable energy (VRE) generation propagates numerous challenges for national energy systems. Despite recent years of VRE expansion and declining coal utilisation in the overall market profile, coal energy generation has maintained and grown its position as a marginal seller in the imbalance market. Coal's disproportionate resurgence as a bidder of later resort in the imbalance market also represents a shift in its bidding behaviour. A comparative breakdown of Britain's overall market with that of Germany, followed by a specific investigation of Britain's imbalance market provides insight into changing roles of VRE, fossil fuelled energy, and compensation technologies. Historically, VRE trends in the British and German markets have been broadly consistent. Recently, increasing distress in Britain's overall market is found to result in the increased use of high pollution technologies to meet imbalances. As a result, the composition of the overall and imbalance markets have increasingly diverged, and although the dominance of gas in the latter is expected, the resurgence of coal energy is more remarkable. Thus, while the proportion of generation by renewables has continued to increase, fossil fuelled (notably including coal) capacity, and its associated infrastructure costs and influence as the price setting marginal seller, remains dominant in the imbalance market.